Rancang Bangun Timbangan Beras Digital Dengan Tampilan Berat Dan Harga Menggunakan Output Suara - Era Madona; Anton anton; Dolla dolla (Teknik Elektro Politeknik Negeri Padang, 2018)
Generally, scales on the market still use manual models which often produce a measurement with the inappropriate result because of the accuracy problem or still have trouble with the level of precision. Furthermore, other measuring instruments are also only pendulum balances or analog scales whose output measurement results are only indicated by the pointer. The results of reading each person have different measurement results. In addition to requiring energy and a long time, the manual weighing process also has a negative impact that can harm consumers where the trader in the market usually cheats in trading. To address this problem, a digital rice weighing device is designed that is controlled by Arduino Uno by using a load cell sensor that having a capacity of 10kg (1/2 - 2.5 liters) which provides a change of resistance when there is a pressure. Changes in resistance can change the output voltage of a load cell. The voltage change that is too small so it is amplified using the HX711 and will convert it to digital in units of weight per liter. The level heavy of rice is calculated at prices corresponding to rice selected through pushbutton. The calculation results are displayed on the LCD if the rice is not enough 1 liter so the price and weight will not be displayed on the LCD. The output sound of Mini Df will mention the price based on the type of rice.